(untitled) (Research, Society and Development, 2020)
The present work aims to analyze social inequality in Brazilian society, considering public policies aimed at education from the legal framework promulgating the universality of education with public funding and the recent political measures to cut resources for education, established since 2016 until the present time. The research was based on the literature on the logic of education as a mechanism to reduce inequality. It was analyzed, in the course of the research, the excerpts of Brazilian laws aimed at guaranteeing education and the reaction to the cuts in government funds of the segments of civil society in charge of social control. As a result, there are numerous losses for the entire student class and education professionals and other services provided by Federal Institutions of higher education corresponding to the federative unit and constituted in the form of universities, institutes and schools of technical and high levels. The study then presented, in its final parameters, the tendency and direction towards the dismantling of public higher education institutions due to the cuts in the most basic resources for their maintenance. Such governmental measures lead to the path of the neoliberal project for the privatization and privatization of these institutions.